Digitalization Of Financial Services And Financial Inclusion In Rural Areas - Rita Ningsih; Yolanda , Yolanda (Jurnal Multidisiplin Indonesia, 2025)
This research examines the relationship between digitalization of financial services and increasing financial inclusion in rural areas of Indonesia. Through a qualitative approach with interviews and observations in three villages in Central Java, the research identifies that limited internet access, low digital literacy, and infrastructure constraints are the main challenges in implementing digital financial services. However, it was found that branchless banking programs, simple digital wallets, and continuous assistance have successfully increased rural communities' access to formal financial services. Strengthening banking agent networks, structured digital literacy training, and supportive policies are needed to ensure sustainable financial inclusion. The results show that digitalization of financial services has the potential to reduce the financial access gap between urban and rural communities when implemented with consideration of local socio-economic conditions.